Host Blood RNA Transcript and Protein Signatures for Sputum-Independent Diagnostics of Tuberculosis in Adults - Sivakumaran, Dhanasekaran; Ritz, Christian; Gjøen, John Espen; Vaz, Mario; Selvam, Sumithra; Ottenhoff, Tom H. M.; Doherty, Timothy Mark; Jenum, Synne; Grewal, Harleen M. S. (Frontiers in Immunology, 2021)
To achieve the ambitious targets for tuberculosis (TB) prevention, care, and control stated by the End TB Strategy, new health care strategies, and diagnostic tools are warranted. Host-derived biosignatures are explored for their TB diagnostic potential by the WHO target product profiles (TPPs) for point-of-care (POC) testing. We aimed to identify sputum-independent TB diagnostic signatures in newly diagnosed adult pulmonary-TB (PTB) patients recruited in the context of a prospective household contact cohort study conducted in Andhra Pradesh, India. Whole-blood mRNA samples from 158 subjects were examined by dual-color Reverse-Transcriptase Multiplex Ligation-dependent Probe-Amplification (dcRT-MLPA) for the expression of 198 pre-defined genes and a Mesoscale discovery assay for the concentration of 18 cytokines/chemokines in TB-antigen stimulated QuantiFERON supernatants. To identify signatures, we applied a two-step approach, in the first step, univariate filtering was used to shortlist potentially predictive biomarkers; this step may be seen as omitting redundant biomarkers. In the second step, a logistic regression approach was used such that group membership became the binary response in a Lasso regression model. We identified an 11-gene and 4-protein signatures that distinguished PTB from household controls with AUCs of ≥ 0.98 (95% CIs: 0.94 – 1.00) and ≥ 0.88 (95% CIs: 0.75 – 1.00), respectively, in our discovery cohort. Subsequently, we evaluated the performance of the 11-gene signature in two external validation data sets viz, an independent cohort at the Glenfield Hospital, Leicester NHS Trust, Leicester, UK (GSE107994 data set), and the catalysis treatment response cohort (GSE89403 data set) from South Africa. The validation of the 11-gene signature distinguished PTB from healthy and asymptomatic M. tuberculosis infected controls in the GSE107994 data set, with an AUC of 0.95 (95% CI 0.91 – 0.98) and 0.94 (95% CI 0.89 – 0.98), but more interestingly in GSE89403 data set, the 11-gene signature distinguished PTB from household controls and other lung diseases with an AUC of 0.93 (95%CI: 0.87 – 0.99) and 0.73 (95%CI: 0.56 – 0.89). The evaluation of our findings meets the WHO TPP benchmarks for a non–sputum-based triage test for TB diagnosis. However, further validation will be required before any clinical implementation.